Properties and Microstructure of Treated Coal Bottom Ash as Cement Concrete Replacement - Moad Alosta; Ahmed Mamdouh; Hussein Al Mufargi; Farah N. A. Abd Aziz; Ahmed Rashid; Otman M. M. Elbasir; Husam Al Dughaishi (Civil Engineering Journal, 2024)
Sustainable construction is a rapidly growing area of research focused on using industrial waste to replace Portland cement in concrete. This approach not only reduces CO2emissions from cement production but also serves as an effective way to diminish the environmental impact of concrete production. This study aims to investigate the properties of Coal Bottom Ash (CBA) after undergoing two different treatments: flotation and burning. It also evaluates the impact of CBA as a cement replacement in concrete with different replacement percentages (5%, 10%, 15%, and 20%). Chemical analysis of CBA has revealed that it can be classified as a pozzolanic material due to its high content of silicates, aluminates, and iron oxides. The microstructure of CBA showed a porous, angular, and irregular surface with many voids. The findings of this study revealed that the optimum mix was 10% CBA, resulting in a 2% increase in compressive strength compared to the control mix after 56 days of curing. Additionally, the study evaluated the effects of sulfate and chloride on concrete. It was found that the mix with the burning treatment showed an overall increase in strength, while the flotation treatment did not reach the control mix's strength in any of the curing periods. Furthermore, the results demonstrated that CBA has significant potential as a cement replacement material, and the burning treatment showed improvement in concrete's overall properties compared to the raw material in terms of mechanical and chemical properties while reducing greenhouse gas emissions and enhancing the environment. Doi: 10.28991/CEJ-2024-010-04-08 Full Text: PDF